A computer vision based approach for stalking detection using CNN-LSTM hybrid model - Iqbal, Shahriar; Hasan, Murad; Faisal, Md Billal Hossain; Neloy, Md.Musnad Hossin; Kabir, Md. Tonmoy (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.